Women, Architecture and Representation in Mamluk Cairo - Karam, Amina (AUC Knowledge Fountain, 2019)
Of the hundreds of documented religious monuments of Mamluk Cairo, known for its intense and often competitive building activity, about twenty are known to be associated with women, at least ten of which still exist in some form. This thesis discusses women's participation in the Mamluk culture of patronage and construction, looking at monuments associated with women not only as a body of work but as the architecture of individual players within the larger building context of Mamluk Cairo. Relying on architectural evidence as well as topographical literature and historical sources, this thesis offers a chronological narrative of women's architecture, divided into five periods; the transitional reign of Shajar al-Durr, the formative period of Baybars and Qalawun, the third reign of al-Nasir Muhammad, his successors of the Qalawunid dynasty, and finally the Circassian Mamluk period. In addition to giving a brief historic overview and outline of significant architectural and urban developments, the narrative focuses on the role of women within the Mamluk class as well as the relation between women and space in public and private domains. Each monument is discussed within its given context, providing an architectural and historic analysis for each entry. The thesis then identifies broader patterns and themes concerning the role and participation of women in architecture, issues of representation as well as possible connections to the pilgrimage ceremony. With the absence of a consistent trend, this thesis demonstrates that the most significant monuments, mainly associated with women related to the reigning sultan, emerge as a response to changing socio-political circumstances, not only representing the associated women but also contributing to the image of the ruling Mamluk household.